Factors Associated with Female Bodily Autonomy in West Pasaman District - Markolinda, Yessy; Ernawati, Ch Tuty; Ramadani, Mery; Husna, Nadiyatul (Jurnal Kesehatan Vokasional, 2025)
Background: Women's involvement in decision-making related to health services has a significant impact on improving maternal and child health, as well as strengthening women's empowerment. In 2022, the Maternal Mortality Rate (MMR) in Pasaman Barat District was 195 per 100,000 live births, ranking first among districts and cities in West Sumatra Province.Objective: This study aims to identify factors associated with women's physical independence in accessing maternal and child health (MCH) services.Methods: This is an analytical study using a cross-sectional design. The sample size was 106 participants.Results: 3.2% of respondents had low independence in utilizing MCH services. Residential area (p-value = 0.038; AOR = 0.321) and knowledge about MCH (p-value = 0.001; AOR = 7.015) were the dominant factors associated with women's physical independence in utilizing MCH services. Meanwhile, husband's education, number of family members, mother's occupation, age group, mother's education, husband's occupation, family income, and access to health facilities were confounding variables in this study.Conclusion: The low level of women's autonomy in utilizing KIA services is primarily influenced by the area of residence and the level of knowledge about KIA. Educational efforts, training of health workers, and cross-sectoral collaboration are needed to improve access and gender equality in health services.